1992
DOI: 10.1007/bf01833330
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor expression in breast cancer epithelium and stroma

Abstract: The insulin-like growth factors (IGFs) are mitogens for many cancer cell types. In breast cancer cells, IGF-I and IGF-II have both been shown to stimulate cell proliferation. However, IGF-I mRNA has not been found in human breast cancer cell lines, making it unlikely that IGF-I is commonly expressed as an autocrine growth factor for breast cancer cells. Nevertheless, IGF-I mRNA can be detected in breast cancer tissue samples, and in situ hybridization studies have shown that the message originates from the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…Although IGF-II has a clearly established role in foetal development (Allan et al, 2001), its function in postnatal life is less understood, despite circulating at a much higher concentration than IGF-I. Although experimental evidence suggests that IGF-II can increase the growth of breast cancer cells in vitro (Cullen et al, 1992) and is upregulated in many breast tumours (Li et al, 1998;Fichera et al, 2000), our results show that circulating IGF-II concentration is not strongly associated with subsequent breast cancer risk in pre-or postmenopausal women, which is consistent with evidence from case -control studies (Holdaway et al, 1999;Li et al, 2001;Yu et al, 2002), although Gr nbaek et al (2004) reported in a prospective study an increase in risk of breast cancer among postmenopausal women with increasing IGF-II, which was of borderline statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Although IGF-II has a clearly established role in foetal development (Allan et al, 2001), its function in postnatal life is less understood, despite circulating at a much higher concentration than IGF-I. Although experimental evidence suggests that IGF-II can increase the growth of breast cancer cells in vitro (Cullen et al, 1992) and is upregulated in many breast tumours (Li et al, 1998;Fichera et al, 2000), our results show that circulating IGF-II concentration is not strongly associated with subsequent breast cancer risk in pre-or postmenopausal women, which is consistent with evidence from case -control studies (Holdaway et al, 1999;Li et al, 2001;Yu et al, 2002), although Gr nbaek et al (2004) reported in a prospective study an increase in risk of breast cancer among postmenopausal women with increasing IGF-II, which was of borderline statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In analogy to uPA, the relationship of PSA to a poor response to tamoxifen therapy, which does not affect PSA expression in vitro (Zarghami et al, 1997), may, for example, be due to a local increase in the concentration of bioavailable IGFs by cleaving IGFBPs (Cohen et al, 1992(Cohen et al, , 1994Figueroa and Yee, 1992;Kanety et al, 1993) through tumour cell-secreted PSA. The free IGFs, abundantly present around the tumour cells because of the focal action of secreted PSA, are potent mitogens for breast cancer cells (Osborne et al, 1989;Cullen et al, 1990). They may disturb the balance and abolish the growth inhibitory effects induced by tamoxifen, despite a reduction in total serum levels of IGFs (Pollak et al, 1990;Lonning et al, 1992;Yee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor I and II (IGF-I and -II) are known as potent mitogens for breast cancer cells (Osborne et al, 1989;Cullen et al, 1990). Binding of IGFs to their binding proteins (IGFBPs) can reduce their mitogenic response (Figueroa and Yee, 1992).…”
mentioning
confidence: 99%
“…Previous studies of IGF-I expression in mammary tissue from rodents (Kleinberg 1997) and humans (Yee et al 1991, Cullen et al 1992) have shown that IGF-I expression is limited to mammary stromal cells. To test whether this was true in prepubertal heifers, we prepared primary mammary epithelial cells from two prepubertal heifers (Weber et al 1999).…”
Section: Expression Of Mammary Igf-i Mrna Is Exclusive To Mammary Stromamentioning
confidence: 99%